1995
DOI: 10.1038/377351a0
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of lin-12-mediated signalling by sel-12, a Caenorhabditis elegans S182 Alzheimer's disease gene

Abstract: The lin-12 and glp-1 genes of Caenorhabditis elegans are members of the lin-12/Notch family of receptors for intercellular signals that specify cell fate. By screening for suppressors of a lin-12 gain-of-function mutation, we identified a new gene, sel-12, which appears to function in receiving cells to facilitate signalling mediated by lin-12 and glp-1. The sel-12 gene encodes a protein with multiple transmembrane domains, and is similar to S182, which has been implicated in early-onset familial Alzheimer's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
450
0
2

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 685 publications
(456 citation statements)
references
References 29 publications
4
450
0
2
Order By: Relevance
“…The existence of a moderate but significant amino acid similarity between the presenilins and spe4, a Caenorhabditis elegans gene involved in the transport and partitioning of cellular constituents during spermatogenes~s, has led to the proposal that the presenilins might participate in intracellular protein transport [1]. Homology with another C. elegans gene sell2 (48% amino acid similarity), which facilitates signalling mediated by lin 12/Notch, suggested that the presenilins might be involved in the transduction pathway of the linl2/Notch family [7].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a moderate but significant amino acid similarity between the presenilins and spe4, a Caenorhabditis elegans gene involved in the transport and partitioning of cellular constituents during spermatogenes~s, has led to the proposal that the presenilins might participate in intracellular protein transport [1]. Homology with another C. elegans gene sell2 (48% amino acid similarity), which facilitates signalling mediated by lin 12/Notch, suggested that the presenilins might be involved in the transduction pathway of the linl2/Notch family [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two mutations were described in a similar gene (67% homologous to PS1), named STM-2, E5-1 or PS2 located on chromosome l [9,10]. The predicted amino acid se-quence encoded in the longest open reading frame composed of 10 exons [7] reveals high similarities with the Caernorhabditis elegans protein SEL-12 [11]. SEL-12 facilitates LIN-12 mediated cell signalling via the Notch family of receptors during development of C elegans.…”
Section: Introductionmentioning
confidence: 99%
“…The biological function of the presenilins remains essentially unknown, but, interestingly, the 103 carboxyl-terminal amino acid residues of PS2 can inhibit apoptosis in a "deathtrap" assay (18). Based on the homology with Caenorhabditis elegans proteins, roles in intracellular protein sorting and/or intercellular signal transmission have been proposed as well (19,20).…”
mentioning
confidence: 99%